2021
DOI: 10.5937/ffr48-31960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooking on the content of carotenoids and tocopherols in sweet corn

Abstract: Taste and nutritional value make sweet corn a valued plant and an important component of the human diet worldwide. Kernel nutritive composition of sweet corn has been reported in various papers, but a description of carotenoid and tocopherols profile, especially after cooking is scarce. Therefore, the present study was carried out to compare the carotenoid and tocopherol content in sweet corn before and after cooking. Contents of b-carotene, lutein+zeaxanthin and tocopherols (d-T, b+g-T, a-T) in the kernels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Similarly, these researchers found that standard yellow/orange kernel dent and popcorn genotypes had a higher content of carotenoids, predominantly β-carotene, lutein, and zeaxanthin. Furthermore, Mladenović-Drinić et al (2021) found high contents of carotenoids and tocopherols in sweet maize hybrids, which were by large genotype-dependent.…”
Section: Cge -Cyanidin-3-glucoside Equivalent; βCe -β-Carotene Equiva...mentioning
confidence: 91%
“…Similarly, these researchers found that standard yellow/orange kernel dent and popcorn genotypes had a higher content of carotenoids, predominantly β-carotene, lutein, and zeaxanthin. Furthermore, Mladenović-Drinić et al (2021) found high contents of carotenoids and tocopherols in sweet maize hybrids, which were by large genotype-dependent.…”
Section: Cge -Cyanidin-3-glucoside Equivalent; βCe -β-Carotene Equiva...mentioning
confidence: 91%